2011
DOI: 10.1523/jneurosci.1791-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable Effects of Natural Image Structure and Color on LFP and Spiking Activity in the Lateral Prefrontal Cortex and Extrastriate Visual Area V4

Abstract: Visual perception is mediated by unique contributions of the numerous brain regions that constitute the visual system. We performed simultaneous recordings of local field potentials (LFPs) and single unit activity (SUA) in areas V4 and lateral prefrontal cortex to characterize their contribution to visual processing. Here, we trained monkeys to identify natural images at different degradation levels in a visual recognition task. We parametrically varied color and structural information of natural images while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…The nature of the relationship between spikes and LFPs is a controversial issue that has attracted much interest (Bauer et al, 1995; Henrie and Shapley, 2005; Mukamel et al, 2005; Kreiman et al, 2006; Liu and Newsome, 2006; Nir et al, 2007; Belitski et al, 2008; Gieselmann and Thiele, 2008; Rasch et al, 2008; Katzner et al, 2009; Khawaja et al, 2009; Xing et al, 2009; Eggermont et al, 2011; Hwang and Andersen, 2011; Jia et al, 2011; Liebe et al, 2011; Lindén et al, 2011; Tsui and Pack, 2011; Zanos et al, 2011b; Lashgari et al, 2012). In a typical experimental scenario, a well-understood property of multi-unit activity (MUA) is compared and contrasted with that of the LFP.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the relationship between spikes and LFPs is a controversial issue that has attracted much interest (Bauer et al, 1995; Henrie and Shapley, 2005; Mukamel et al, 2005; Kreiman et al, 2006; Liu and Newsome, 2006; Nir et al, 2007; Belitski et al, 2008; Gieselmann and Thiele, 2008; Rasch et al, 2008; Katzner et al, 2009; Khawaja et al, 2009; Xing et al, 2009; Eggermont et al, 2011; Hwang and Andersen, 2011; Jia et al, 2011; Liebe et al, 2011; Lindén et al, 2011; Tsui and Pack, 2011; Zanos et al, 2011b; Lashgari et al, 2012). In a typical experimental scenario, a well-understood property of multi-unit activity (MUA) is compared and contrasted with that of the LFP.…”
Section: Introductionmentioning
confidence: 99%
“…Although neural activity in V4 has been related to color and shape processing of visual objects [13][14][15][16] and visual attention 17 , neural responses in lPF have been traditionally associated with working memory, that is, the short-term maintenance and manipulation of sensory information in memory tasks 18,19 . More recently, however, an increasing number of studies have found that the neural circuitry underlying short-term retention of sensory information likely entails earlier sensory cortical areas as well 20 .…”
mentioning
confidence: 99%
“…It is likely that V4 plays a critical role. V4 is implicated in color vision (Zeki, 1980 ; Wade et al, 2008 ) in both monkey (Zeki, 1983a ; Wild et al, 1985 ; Brewer et al, 2002 ; Conway and Tsao, 2006 ) and human brains (Zeki et al, 1991 ; McKeefry and Zeki, 1997 ; Wade et al, 2008 ; Goddard et al, 2011 ; Liebe et al, 2011 ; Lofar-Sousa et al, 2016 ) and the responses of cells in it can be selective for hues (Zeki, 1980 ; Conway et al, 2007 ; Brouwer and Heeger, 2013 ). As well, an imaging study of activity in cortical areas which correlate with the perception of colored after-images pinpointed V4 (Sakai et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%